A qualitative study to explore the attitudes of women and obstetricians towards caesarean delivery in rural Bangladesh - Begum, Tahmina; Ellis, Cathryn; Sarker, Malabika; Rostoker, Jean-Francois; Rahman, Aminur; Anwar, Iqbal; Reichenbach, Laura (BMC, 2022)
This article was published in the BMC Pregnancy and Childbirth [© The Author(s). 2018 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/) ] and the definite version is available at: https://doi.org/10.1186/s12884-018-1993-9 The Journal's website is at: https://bmcpregnancychildbirth.biomedcentral.com/articles/10.1186/s12884-018-1993-9#citeas